2017
DOI: 10.1093/scan/nsx099
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of empathic accuracy in adolescence

Abstract: Empathy, the ability to understand others’ emotions, can occur through perspective taking and experience sharing. Neural systems active when adults empathize include regions underlying perspective taking (e.g. medial prefrontal cortex; MPFC) and experience sharing (e.g. inferior parietal lobule; IPL). It is unknown whether adolescents utilize networks implicated in both experience sharing and perspective taking when accurately empathizing. This question is critical given the importance of accurately understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 52 publications
3
36
2
Order By: Relevance
“…These areas are associated with perspective taking or ToM [69] and partly overlap with the default mode network (DMN) [35]. We propose that higher activity in these areas reflects perspective-taking processes [30], which are neces-sary to understand speaker intention in the affective dialogues. On the other hand, understanding speaker intention is not necessary when following informative or the direct dialogues, neither of which activated the ToM network, even when compared to baseline.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These areas are associated with perspective taking or ToM [69] and partly overlap with the default mode network (DMN) [35]. We propose that higher activity in these areas reflects perspective-taking processes [30], which are neces-sary to understand speaker intention in the affective dialogues. On the other hand, understanding speaker intention is not necessary when following informative or the direct dialogues, neither of which activated the ToM network, even when compared to baseline.…”
Section: Discussionmentioning
confidence: 96%
“…Recent meta analyses have shown that the DMN overlaps with ToM areas in humans [1,35] and macaques [35] and that the precuneus, together with the dmPFC, is associated with perspective taking, as well as self-referential and autobiographical processing [1]. When adolescents are tracking other people's feelings, activity in the precuneus correlates with performance accuracy [30], and empathy training in adolescents results in strengthened connectivity between the precuneus and the vmPFC [31]. Finally, the precuneus is more engaged during indirect compared to direct speech processing in adult listeners [5,22,27,55,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between parents' and adolescents' anterior insula activation provides initial evidence for parental influences on ER and empathy development on a neurobiological level. A past study of adolescents found that activation of the dorsomedial prefrontal cortex and vmPFC was associated with empathic accuracy (Kral et al, 2017), indicating that these regions are not simply involved in feeling empathic but are needed to correctly assess another person's feelings. Yet another empathyrelated region activated by the error condition was the caudate.…”
Section: Discussionmentioning
confidence: 99%
“…Fisher's r to z conversion was then used to convert correlation coefficients to zscores (See Figure 1). Similar procedures to previous EAT studies were followed for calculating empathic accuracy ratings in order to maintain fidelity with previously reported results in other populations (Kral et al, 2017;J. Lee et al, 2011;Mackes et al, 2018;Zaki et al, 2009).…”
Section: Empathic Accuracy Behavioural Analysismentioning
confidence: 99%